A filosofia e seu ensino podem colaborar para adiar o fim do mundo? - Garcia, Amanda Veloso (Editora Oficina Universitária, 2022)
The book hypothesizes that teaching philosophy needs to be rethought to deal with the urgent times we live in, breaking with the Eurocentric approach and the conception of rational humanity that underpins fascism and speciesism that destroy living conditions on the planet. With an ecological philosophical perspective, an understanding of the teaching of philosophy is defended in a way that is entangled with the context and the beings that, like us, make up the environment, having as teachers of life the soil, trees, herbs, bacteria, fungi, microorganisms and mangroves. A philosophizing-with connected with the future of life on the planet through lines of flight from the ideologies of superiority of a type of humanity, learning from the wisdom of the earth in the form of an ecosophy that articulates ethics, politics and aesthetics as dimensions of the same perception of existence.